The right to inclusive education in Nigeria: meeting the needs and challenges of children with disabilities (2010)
The article examines the right to inclusive education in Nigeria. It asserts that the essence of the right to education is that it should be provided to all and without discrimination. It posits that, under Nigerian law, children with disabilities suffer many prejudices, including seclusion and discrimination in terms of education. It argues that such practices amount to a violation of the Nigerian commitments and obligations under international law to provide education for all and without discrimination. The article calls on the Nigerian government to put in place adequate laws and policies advancing the right of children with disabilities within its territory.